2016
DOI: 10.1021/acsbiomaterials.6b00245
|View full text |Cite
|
Sign up to set email alerts
|

Amino-Acid-Incorporating Nonionic Surfactants for Stabilization of Protein Pharmaceuticals

Abstract: With the rapid development of protein-based pharmaceutical products over the past decade, one of the biggest challenges in product development is maintaining the structural stability of proteins during purification, processing, and storage. In this work, the design of a new class of surfactants, polyethermodified N-acyl amino acids, is presented. One surfactant from this series, containing a phenylalanine moiety, demonstrated remarkable stabilization against aggregation of several model protein drugs. Dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
2
17
0
Order By: Relevance
“…Surfactant synthesis was adapted from Katz et al Full synthetic procedures are included in the Supporting Information. In brief, phenylalanine was acylated with a hydrocarbon chain acyl chloride at room temperature in the presence of a base.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Surfactant synthesis was adapted from Katz et al Full synthetic procedures are included in the Supporting Information. In brief, phenylalanine was acylated with a hydrocarbon chain acyl chloride at room temperature in the presence of a base.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research of Katz et al identified a new amino acid-based surfactant without ester bonds, commonly referred to as FM1000, that often outperforms the current surfactants on the market used for protein stabilization. , (For this paper, FM1000 will hereafter be referred to as 14FM1000, where the number in front of “FM1000” denotes the hydrophobic tail length.) FM1000 is currently in development by DuPont Pharma Solutions as a new excipient for the pharmaceutical industry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymer excipients are inactive ingredients included in pill formulations that are frequently, but not exclusively, used to sequester small molecules and larger payloads through noncovalent interactions with active pharmaceutical ingredients (APIs), , proteins, and polynucelotides . In oral, intravenous, or intramuscular administration, the polymer works with the active ingredients as a stabilizer, both on the shelf and in vivo.…”
mentioning
confidence: 99%
“…The nonionic surfactant plays a pivotal role in stabilizing the protein in commercial formulations over the ionic surfactants; however, the mechanism of this stabilization is not clearly established [39,40]. Katz et al [41] reported that the amino acid-based nonionic surfactants are promising one for stabilization of protein pharmaceuticals. Kishore and coworkers recently focused on the understanding of interactions of nonionic surfactants with proteins in biotherapeutic formulations [42].…”
Section: Pharmaceuticals and Cosmeticsmentioning
confidence: 99%